SRF material research using muon spin rotation and beta-detected nuclear magnetic resonance - Junginger, Tobias; Laxdal, Robert; MacFarlane, W. A.; Suter, Andreas (Frontiers in Electronic Materials, 2024)
Muon spins precess in transverse magnetic fields and emit a positron preferentially in the spin direction at the instant of decay, enabling muon spin rotation (µSR) as a precise probe of local magnetic fields in matter. µSR has been used to characterize SRF materials since 2010. At TRIUMF, a beam of 4.2 MeV µ + is implanted at a material-dependent depth of about 150 µm. A dedicated spectrometer was developed to measure the field of first vortex penetration and pinning strength in SRF materials in parallel magnetic fields of up to 300 mT. A low energy beam available at PSI implants µ + at variable depth in the London layer allowing for direct measurements of the London penetration depth from which other material parameters relevant for SRF applications, such as the lower critical field and the superheating field, can be calculated. Beta-detected nuclear magnetic resonance (β-NMR) is a technique similar to low energy µSR using beams of low-energy β radioactive ions. With a recent upgrade, it is capable of detecting the penetration of parallel magnetic vortices, depth resolved with nanometer resolution at applied fields of up to 200 mT. In this paper, we review the impact and capabilities of these techniques for SRF research.